Evaluation of the cytotoxic activity of leaf extracts of Mimosa rubicaulis (Lam.) against cancer (HepG2) and normal (L929) cells through induction of apoptosis: Cytotoxic and apoptosis activities of Mimosa rubicaulis leaf extracts in HepG2 cancer and L929 normal cell lines - Tamboli, Ashpak M.; Wadkar, Kiran A.; Tamboli, Naziya A.; Manure, Javeed Y.; Bagwan, Salma A. (Iranian Journal of Pharmaceutical Sciences, 2024)
Investigation of the in-vitro anti-cancer and apoptosis activity of various extracts of M. rubicaulis (Lam.) against cancer cell lines (HepG2 and L929) is important. The HepG2 and L929 Cell lines were exposed to increasing concentrations of various extracts of leaves of M. rubicaulis (Lam.) ranging from 640 to 20 µg/ml for 24 hours. MTT assay was used to determine cytotoxicity. All extracts of leaves of M. rubicaulis (Lam.) treated with cancer cell lines HepG2 and normal cell line L929 in response to increasing concentration, cell viability decreased significantly. Additionally, the most affected cells were HepG2 cells, followed by L929. The study found that when exposed to ethanolic extract, the cancer cell lines (HepG2) showed the highest expression, while the normal cell lines (L929) showed the lowest. Based on the experimental data, we discovered that M. rubicaulis (Lam.) has a cytotoxic effect on cancer cell lines. In contrast, no cytotoxic effect was observed at the highest dose on normal cells. The ethanolic extract had potent anti-cancer activities against HepG2 cells via induction of Apoptosis by Flow Cytometry. According to the findings ethanolic extract has a high cytotoxicity against HepG2 cells, with an IC50 of 93.69 µg/ml. Apoptosis processes such as alterations in cell shape, chromatin condensation, membrane swelling, and the production of apoptotic bodies were seen in ethanolic extract treated HepG2 cells. The ethanolic extract treated HepG2 cells variations in light scattering reveal the general characteristics of cell death due to apoptosis. These outcomes show how effective ethanolic extract of M. rubicaulis (Lam.) to exert apoptosis, particularly in late stage apoptosis in HepG2 cell lines. Hence, further investigation is required to study the phytoconstituents in ethanolic extract of M. rubicaulis (Lam.) responsible for cytotoxic activity.